Studies in law, politics and society. Vol. 32 - Sarat, Austin; Ewick, Patricia (Amsterdam ; London : JAI, 2004)
This volume presents articles by an interdisciplinary and international group of scholars spanning the social sciences, humanities, and law. It examines new perspectives on political relationships, politics and legal reform, and law and the family.
Interdisciplinarity in legal scholarship : critical theories of identity and performance. Forces of consent / Susan R. Schmeiser -- Critical race theory's dream narratives : a method for an anti-racist social science? / Joshua M. Price -- The Socratic screenplay : law, allegory and science fiction in John and Joyce Corrington's screenplays for The omega man and Battle for the planet of the apes / Lenora Ledwon. Policy and practice : legal institutions and the law in action. Foundations of constitutional legitimacy : legal-political culture, constitutional aptness, and baseline community / Zehava Zevit -- Mother and children : caught in the warzone / Jacqueline Goodman -- A political account for legal confrontation between state and society : the case of Israeli legal pluralism / Yüksel Sezgin.
Description based on print version record.
Keywords: Sociological jurisprudence; Political sociology; Law & society; Law -- General